Quality of Service and Satisfaction Level of Non-National Health Insured Inpatients at K Referral Center Hospitals - Widyaputri, Anak Agung Ayu Wanda; Sriatmi, Ayun; Budiyanti, Rani Tiyas (Journal of Public Health for Tropical and Coastal Region, 2025)
Introduction: The results of the community satisfaction survey at K Referral Center Hospital in 2019-2023 showed a decrease in patient satisfaction. In inpatient installation, satisfaction levels reached only 83.53% in May 2024, below the minimum standard of 90% set by the Ministry of Health (Kepmenkes Number 129 / Menkes / SK / II / 2008) for inpatient care. This study aimed to identify the level of satisfaction regarding the quality of inpatient services among non-national health insurance patients.Methods: This was a cross-sectional quantitative study. Sample calculation using the proportional sampling technique with accidental data collection for 97 non-national health-insured inpatients in January-February 2025. Data were processed using the chi-squared relationship test with SERVQUAL variables.Results: Most patients were satisfied (60.8%) with the services they received, whereas the others were dissatisfied (39.2%). A significant relationship was found between the tangible dimensions, responsiveness, reliability, and patient satisfaction. No significant relationship was found between the dimensions of empathy, assurance, and patient satisfaction.Conclusion: Inpatients satisfaction in K referral Hospital is related to the facilities owned by the hospital, attitudes of medical personnel, speed of response to complaints, and reliability of officers in providing services that can increase trust in health services